E-Commerce in Tourism: Practice, Problems, Perspectives - Yevhen Kozlovskyi (Вісник Київського національного університету культури і мистецтв. Серія: Туризм, 2018)
The article is devoted to the consideration of the problem in using modern e-commerce tools in the field of tourism. In order to disclose the topic, methods of objectivity and system are used to establish the main advantages and disadvantages of using e-commerce in the economic activity of a tourist enterprise. The purpose of the article is to determine the state and prospects for the development of e-commerce in the tourism services market, as well as the analysis of international experience in the field of e-commerce legislative regulation. Together with the rapid spread of electronic payment, the communication networks development and the growing number of potential Internet users, e-commerce has become one of the most important sales channels for tourism services, while increasing the profitability and competitiveness of enterprises. One of the important factors that hinders the rapid spread of e-tourism in Ukraine is the regulatory framework imperfection. After the introduction of existing mechanisms in interaction between the seller and the consumer in tourism services, electronic sales can be made one of the modern and effective ways to implement a tourism product.